Metonymy of Human Body Organs in Indonesian - I Dewa Putu Wijana (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2022)
This paper will try to describe the human body parts used to express metonymy, and associative patterns which hold between the target domains and the meanings intended by the expressions. By using data collected from Indonesian Big Dictionary added metalinguistic ones whose gramaticalilty and acceptability have been tested empirically to other Indonesian natives. The research found that thare are many human body parts which can be used metonymically, and they can perform various patterns of associative relations, such as part-whole, part-whole, container-contained, instrument-function, symbol-symbolized, and iconic association. Several body parts can be used more than one association, and metaphor and metonymy problems still can not be clearly cut.